Gut microbiota-derived short-chain fatty acids regulate gastrointestinal tumor immunity: a novel therapeutic strategy? - Dong, Yue; Zhang, Kexin; Wei, Jingge; Ding, Yiyun; Wang, Xin; Hou, Huiqin; Wu, Jingyi; Liu, Tianyu; Wang, Bangmao; Cao, Hailong (Frontiers in Immunology, 2023)
Tumor immune microenvironment (TIME), a tumor-derived immune component, is proven to be closely related to the development, metastasis, and recurrence of tumors. Gut microbiota and its fermented-metabolites short-chain fatty acids (SCFAs) play a critical role in maintaining the immune homeostasis of gastrointestinal tumors. Consisting mainly of acetate, propionate, and butyrate, SCFAs can interact with G protein-coupled receptors 43 of T helper 1 cells or restrain histone deacetylases (HDACs) of cytotoxic T lymphocytes to exert immunotherapy effects. Studies have shed light on SCFAs can mediate the differentiation and function of regulatory T cells, as well as cytokine production in TIME. Additionally, SCFAs can alter epigenetic modification of CD8+ T cells by inhibiting HDACs to participate in the immune response process. In gastrointestinal tumors, the abundance of SCFAs and their producing bacteria is significantly reduced. Direct supplementation of dietary fiber and probiotics, or fecal microbiota transplantation to change the structure of gut microbiota can both increase the level of SCFAs and inhibit tumor development. The mechanism by which SCFAs modulate the progression of gastrointestinal tumors has been elucidated in this review, aiming to provide prospects for the development of novel immunotherapeutic strategies.